DEVELOPMENT OF MEDIA CAD RICHPEACE GRADING SYSTEM FOR THE MAKING OF HOME CLOTHING PATTERN IN FASHION EDUCATION STUDY PROGRAM, MEDAN STATE UNIVERSITY - Surniati Chalid; Nurhayati Tanjung; Yudhistira Anggraini; Eka Rahma Dewi (International Journal of Innovative Technologies in Social Science, 2022)
The aims of this study were (1) to find out how to develop the CAD Richpeace Grading System media for making home dress patterns at the Fashion Design Study Program, Medan State University. (2) Knowing the feasibility of CAD Richpeace Grading System media in making home dress patterns at the Fashion Design Study Program, Medan State University. This research is development research (R&D). The development model used in this study is the ADDIE development framework. The validation results by material experts obtained a score of 84.8% in the good category and the validation results by media experts obtained a score of 87.72% in the very good category. Small group trials were conducted on 8 students of the fashion design education study program. student assessment results in small group trials of 80.60% with good criteria. Group trials are being carried out by 16 students obtaining 85.23% in the very good category. Next is the large group tryout which was conducted on 32 students of the fashion education study program with the results of the student assessment in the large group test being 88.19% with very good criteria. From the results of the assessment of media experts, material experts, small group and large group trials, it can be concluded that the Cad Richpeace Grading System media developed for making home clothes for garment businesses is very suitable for use as learning media and can help students to understand the material and understand steps in making home fashion patterns with a digital grading system.